Evaluation of the Effect of Comorbidity on the Efficacy and Safety of β-Lactam Antibiotics in Patients with Community-Acquired Pneumonia - O. V. Muslimova; E. A. Sokova; A. B. Prokofiev; M. V. Zhuravleva; A. V. Shapchenko; T. V. Alexandrova (Безопасность и риск фармакотерапии)
Lower respiratory tract infections, which include community-acquired pneumonia (CAP), are the most common cause of death among all infectious diseases. The presence of a comorbid pathology in a patient with CAP suggests a possibility of mutual influence and changes in the course of both the underlying disease and comorbidities, as well as changes in the effectiveness and safety of ongoing drug therapy. The aim of the study was to analyse literature data on the structure of comorbidity in CAP patients and its impact on the efficacy and safety of therapy with β-lactam antibiotics. It has been established that CAP most often occurs in patients with chronic obstructive pulmonary disease, cardiovascular diseases (ischemic heart disease, arterial hypertension, and chronic heart failure), cerebrovascular disease, chronic kidney disease, diabetes mellitus, bronchial asthma, leukemia, anemia, dementia, neurological disorders, and cancer. The most common causative agent of CAP, regardless of the patient’s age and comorbidity, is pneumococcus (Streptococcus pneumoniae), followed by intracellular pathogens (mycoplasmas, chlamydia) and Haemophilus influenzae, as well as respiratory viruses. With this in mind, the initial empiric therapy for CAP mainly includes β-lactam antibiotics, which are effective against pneumococcus. If patients with CAP have concomitant chronic diseases and conditions, the spectrum of pneumonia pathogens may differ from that in the general population and include rare pathogens and multidrug-resistant strains. The effectiveness of antibiotic therapy in such patients is reduced, which leads to a worsening of the course of both CAP and concomitant diseases. This patient population may require longer treatment with antibiotics, including β-lactams, or the use of antibiotics at doses that provide a higher minimum inhibitory concentration, which is associated with a high risk of adverse reactions and a decrease in the safety of antibiotic therapy.